The interplay between cognitive ability, alcohol consumption, and health characteristics. Issue 12 (14th December 2017) - Degerud, E.; Ystrom, E.; Tambs, K.; Ariansen, I.; Mørland, J.; Magnus, P.; Davey Smith, G.; Næss, Ø.
Abstract: Background: Higher cognitive ability is associated with favourable health characteristics. The relation between ability and alcohol consumption, and their interplay with other health characteristics, is unclear. We aimed to assess the relationship between cognitive ability and alcohol consumption and to assess whether alcohol consumption relates differently to health characteristics across strata of ability. Methods: For 63 120 Norwegian males, data on cognitive ability in early adulthood were linked to midlife data on alcohol consumption frequency (times per month, 0–30) and other health characteristics, including cardiovascular risk factors and mental distress. Relations were assessed using linear regression and reported as unstandardised beta coefficients [95% confidence interval (CI)]. Results: The mean ±s.d. frequency of total alcohol consumption in the sample was 4.0 ± 3.8 times per month. In the low, medium, and high group of ability, the frequencies were 3.0 ± 3.3, 3.7 ± 3.5, and 4.7 ± 4.1, respectively. In the full sample, alcohol consumption was associated with physical activity, heart rate, fat mass, smoking, and mental distress. Most notably, each additional day of consumption was associated with a 0.54% (0.44–0.64) and 0.14% (0.09–0.18) increase in the probability of current smoking and mental distress, respectively. In each strata of ability (low, medium, high), estimates were 0.87% (0.57–1.17), 0.48% (0.31–0.66) and 0.49% (0.36–0.62) for current smoking, and 0.44% (0.28–0.60), 0.10% (0.02–0.18), and 0.09% (0.03–0.15) for mental distress, respectively. Conclusions: Participants with low cognitive ability drink less frequently, but in this group, more frequent alcohol consumption is more strongly associated with adverse health characteristics.